La enseñanza de lenguas extranjeras en Argentina - Pozzo, María Isabel (Diálogos Latinoamericanos, 2009)
This article seeks to present an overview of the current situation in foreign language teaching in Argentina, in a crucial moment in which the implementation of an educational reform asks for an evaluation of achievements and difficulties of previous legislation. As languages represent a heterogeneous group with diverse ideological connotations, this study examines the most studied foreign languages in the country. The revision comprises some aspects in common with native language teaching as well as the situation of aboriginal language teaching. External conditions such as the monolingual context, the role of Argentina in MERCOSUR and national linguistic policies are also considered in this article as they are part of the foreign language teaching scene.